Evaluación de la eficiencia de la Panta de Tratamiento del Agua Potable y propuesta de repotenciación en la Loma de Alcoceres del Barrio San Martín de la Parroquia Juan Montalvo del cantón Latacunga de la provincia de Cotopaxi en el período octubre 2018-agosto 2019. - Cando Zapata, Andrea Michael (2019)
The purification of water consists of the elimination of volatile compounds, followed by the precipitation of impurities with flocculants, filtration and disinfection with chlorine. The objective of this investigation was to evaluate the processes and analysis of the water treatment plant Loma de Alcoceres (LA) located in the San Martin neighborhood, Latacunga canton. To do this, the physical-chemical and microbiological analysis of the water at the entrance and exit of the plant, and in the distribution network was carried out. Thus, as the annual evaluation of residual chlorine parameters, total coliforms, fecal coliforms and Escherichiacoli for the period 2010-2015 and 2017-2019. The results allowed to identify that the water quality at the outlet of the (LA) plant is in accordance with the provisions of book VI Annex 1 Table 2 of the TULSMA. However, the water is slightly hard, which could cause clogging of the pipe due to the accumulation of sediments, the accumulation process is slow, but it can be harmful if it accumulates in the pipes or pipes through which water enters and exits from domestic appliances. The treatment plant is operating with an efficiency of 99.81% for an annual average.